Adam Smith @ 300 - Blomert, Reinhard 1951-; Föllinger, Sabine 1963-; Horn, Karen 1966-; Kurz, Heinz D. 1946-; Nellinger, Ludwig 1956-; Paganelli, Maria Pia 1972-; Priddat, Birger P. 1950-; Rössner, Philipp Robinson 1977-; Schumacher, Reinhard (Duncker & Humblot, 2024)
This volume provides a detailed overview of the current state of economic and non-economic research on Adam Smith. It takes a closer look at the economic and social conditions in Scotland at the time of Smith as well as at the influence of classical philosophy on his thinking. Smith's work is contrasted with other important scientific research programs, such as those of Hume, Fichte, Hegel, Thünen, Marx and Schumpeter.
Keywords: Smith, Adam -- 1723-1790; Wirtschaftsentwicklung; Wirtschaftstheorie; Klassische Nationalökonomie; Konferenzschrift -- 2023 -- Musselburgh